THE STUDY OF THE FUNCTIONAL STATE OF MOVEMENT SUPPORT SYSTEMS IN ATHLETES - Rulenko, V. V.; Bogdanovska, N. V.; Boichenko, C. Yu. (Rehabilitation and Recreation, 2024)
Aim is to study and assess the impact of sports on the functional state of the movement support systems in athletes of different sports in order to determine the dynamics of these indicators during training. Materials. The study involved 10 athletes of different sports, aged 18 to 35 years. Athletes were divided into 3 groups: the group of strength sports (weightlifting, powerlifting), the group of speed-strength sports (short-distance running, jumping) and the group of endurance sports (long-distance running, swimming). The groups performed individual training complexes to improve the functional state of the movement support systems. Results. The results of the study showed that the functional state of the movement support systems in athletes improved during 1 month of training. This was observed for all indicators that were assessed. In athletes who were involved in strength sports, muscle strength increased the most. In athletes who were involved in speed-strength sports, muscle contraction speed increased the most. In athletes who were involved in endurance, overall endurance increased the most. All groups showed a statistically significant improvement compared to their baseline data. Conclusions. Sports have a positive impact on the functional state of the movement support systems in athletes of different sports. This was observed for all indicators that were assessed. The greatest changes were observed in the indicators of the functional state of the muscular system. In order to improve the effectiveness of sports training, it is necessary to individually select the load and training regime in accordance with the sport, the level of training of the athlete and his individual characteristics.